STATE POLICY AS TO DEVELOPMENT STRATEGY OF URBANIZED TERRITORIES OF SMALL HISTORICAL TOWNS - Kravchenko S.G. (Pressing Problems of Public Administration, 2015)
The condition of the urbanized territories of small historical towns, and strategic vision ofthe role of sights of the national value in forming the urban environment have been analyzed. Thespecificity of the sights’ impact on the urbanized territories development is discussed. Theinfluence of the state policy on the strategy of small historic towns’ development has beenresearched. The ways are suggested to preserve and maintain the sights for future use, as well asthe main lines of further development of territories adjacent to or located within the zones ofhistorical habitats are outlined.